Propuesta de mejora de los puntos críticos de control identificados durante el proceso de elaboración de la lechona en la fábrica Thiago’s (2021)
The safety of food within the agri-food chain is a responsibility of all the participating links and even more so for the final link, which is the consumer, who must demand that the preparation of food is suitable and does not represent a risk to human health. This degree project was carried out from the premise of elaborating and producing food in optimal conditions for human consumption, for this reason the HACCP method was used to generate a greater commitment on the part of the operators and the owner, in guaranteeing the compliance with the aspects of Resolution 2674 of 2013 in Lechoneria Thiago`s. For this, an initial diagnosis of the factory was carried out with the help of tools such as the checklist, which made it possible to determine the percentage of compliance of the factory, with respect to the aforementioned resolution; Subsequently, the factors that influence noncompliance were analyzed and identified through a fishbone diagram, during the development of the work it was necessary to develop the flow diagram of the production process, which allowed determining the risks, dangers and critical control points, to establish their critical limits and to be able to generate improvement actions to achieve sanitary compliance in accordance with current regulations, the completion of this work would be impossible without the participation and accompaniment of the operators through the surveys carried out, as well as their owner